Analisis Kondisi Financial Distress pada PT. Indofarma Tbk. Periode 2022-2024 - Ellin Ellin; Ade Lisa Matasik (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2025)
This study aims to analyze the financial distress condition of PT Indofarma Tbk during the period of 2022-2024 using the Modified Altman Z-Score Model. The research employs a quantitative approach and utilizes secondary data obtained from the company's annual financial reports published by the Indonesia Stock Exchange. Four key ratios in the Modified Altman Z-Score Model are used to assess the level of financial distress risk, namely: working capital to total assets (X1), retained earnings to total assets (X2), earnings before interest and taxes to total assets (X3), and book value of equity to total debt (X4). The results show that PT Indofarma Tbk's Z-Score value has been well below the threshold of 1.1 for three consecutive years, at -4.97 in 2022, -21.40 in 2023, and -27.19 in 2024. These values indicate that the company is in a serious financial distress condition, with a high risk of bankruptcy. Contributing factors include negative working capital, continuous operational losses, increasing debt levels, and a decline in the company's equity.